Review of the Characterization of Lactic Acid Bacteria in Tuna Fish - Malikha, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Bekasam is a type of fermented freshwater fish product with sour taste. Bekasam is made from fish that have been cleaned gills and entrails, washed, mixed with salt. After 2 days of fermentation, rice is added to this mixture and fermentation is continued for 5 to 7 days. Bekasam is thought to have antihypertensive activity due to the formation of bioactive peptides resulting from fish protein degradation during the fermentation process of the scars. This study aims to isolate indigenous lactic acid bacteria with high power. Lactic acid bacteria were isolated from tuna. Isolation was carried out using MRS agar + CaCO3 medium and screening of proteolytic lactic acid bacterial isolates was carried out using skim agar. Colonies that provide a clear zone on the skim to be identified as lactic acid bacteria. Of the 180 isolates of acid-producing bacteria that provide clear zones in the MRS to find 150 strains of lactic acid bacteria. The results of further morphological and biochemical tests indicate that these isolates are genera Lactobacillus, Pediococccus and Leuconostoc. The results of further selection were carried out on homofermentative lactic acid bacteria and had high proteolytic activity. The results of identification of isolate species using API CH50 showed that selected lactic acid bacteria were Lactobacillus plantarum, Lactobacillus pentosus, and Pediococcus pentosaceus